GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA DESA SUKA DAMAI KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI TAHUN 2021-2022 - Nugroho, Wahyu Nugroho; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research discusses the transformational leadership style possessed by the Suka Damai Village Head. Looking at the Developing Village Index data in 2022, Suka Damai Village has succeeded in obtaining independent village status which was obtained within 1 year. In the Village Development Index there are 3 main indices consisting of the social resilience index, the economic resilience index and the environmental resilience index. This research also wants to prove whether the transformational leadership style of the Head of Suka Damai Village can encourage an increase in the independent village status obtained by Suka Damai Village. The research methodology used by the author is descriptive qualitative. The type of data used is primary obtained through an interview process and secondary data comes from documents related to research. This research uses theory according to Suwatno (2019), namely, showing ideal influence, generating inspirational motivation, providing intellectual stimulation, and treating followers by providing individual attention. The method used in this research is a qualitative descriptive method, data collection techniques are by observation, interviews and documentation. The results of the research show that the transformational leadership style of the Head of Suka Damai Village is good in implementing 4 aspects, namely, showing ideal influence by providing a good example so that his followers can emulate, generating inspirational motivation, which is a motivating step which is very important in providing enthusiasm and trust. themselves for their followers, providing intellectual stimulation, providing space for followers to be more creative in looking at a problem and providing space to think together, and treating followers by providing individual attention which can strengthen the relationship between the leader and followers so that the leader can absorb every need of the leader. each of his followers. Keywords : Transformational Leadership Style, Village head.